Preliminary study: human trampling effects on seagrass density. (November 2019) - Nurdin, N; Nafie, Y La; Umar, M T; Jamal, M; Moore, A
Abstract: This preliminary study performed a small-scale experimental evaluation of the effects of trampling on tropical seagrass meadows. The study site was Barrang Lompo Island, in the Spermonde Archipelago, South Sulawesi, Indonesia. The experimental design comprised two trampling treatments (trampling by an adult and by children) and a control plot (no trampling). The trampling was carried out daily over a three week period. After trampling (adult or children), the detached seagrass leaf biomass was higher than uprooted seagrass biomass. Trampling by an adult had a greater effect on seagrass density than trampling by children. Three weeks after trampling ceased, both treatment plots exhibited substantial recovery, with final density closer to control density in the plot trampled by children.